The Influence of the Approach of Realistic Mathematics and Motivation to Learn Mathematics Students On the Ability of Mathematical Modeling Students On Cubes and Beams in MTs Al-Majidiyah - Herman Mawengkang (International Journal Of Humanities Education and Social Sciences (IJHESS), 2021)
This study aims to determine: (1) Whether the increased ability of the mathematical modeling of students who are taught with Realistic Mathematics learning is higher than students taught by expository (2) Whether there is interaction between learning motivation of student learning on the ability of the mathematical modeling students (3) How the process of resolving questions related to the ability of the mathematical modeling of the students on the Realistic Mathematics learning and expository. This research is a quasi experiment with research population is all students of class VIII MTs Al-Majidiyah Chart Stone. The sample in this research is class VIII A and VIII class B. The instrument used consisted of: (1) test the ability of mathematical modeling with the material of the cube and beam (2) pieces of the Question. The Data in this research were analyzed by using descriptive statistical analysis, analysis and parametric statistics. Statistical analysis of data was done with the t test analysis and anova 2 lines. The results showed that: (1) Increase the ability of the mathematical modeling of students who are taught with learning PMR higher than students taught by expository (2) there is No interaction between the learning that is used with the learning motivation of the students to the ability of the mathematical modeling student (3) the Process of the completion of the answers of students who are taught by using learning model PMR is better compared to the expository